DEVLOPMENT AND INVITRO EVALUATION OF NANOSUSPENSION GEL OF BENZOYL PEROXIDE - Ancheria, Rahul Kumar; Jain, Saloni; Kumar, Deepak; Soni, Shankar Lal (Asian Journal of Pharmaceutical Research and Development, 2019)
Novel drug delivery systems are designed with an intend to deliver drugs to the specific site at a rate and extent directed by the needs of the body and it directs an active entity to specific site of action during the period of treatment. Acne vulgaris is a common skin disease, affecting about 70-80% of adolescents and young adults. It is a multifactorial disease of the pilosebaceous unit. it has been developed as possible carriers to deliver antifungal drugs to the target site and to enhance an epidermal permeation across the skin.this article we present benzoyl peroxide can increase solubility and permeability of topical used.when benzoyl peroxide is very widely used in the mild to moderate acne vulgaris and rosacea. KEYWORDS-